Exploring the role of external experts in supporting staff to implement psychosocial interventions in care home settings: results from the process evaluation of a randomized controlled trial - Claire A. Surr; Emily Shoesmith; Alys W. Griffiths; Rachael Kelley; Joanne McDermid; Jane Fossey (BMC, 2019)
Abstract Background Psychosocial interventions offer opportunities to improve care for people with dementia in care homes. However, implementation is often led by staff who are not well prepared for the role. Some interventions use external experts to support staff. However little is known about external expert, care home staff and manager perceptions of such support. This paper addresses this gap. Methods Multi-methods study within a process evaluation of a cluster randomised controlled trial of Dementia Care Mapping™ (DCM). Interviews were conducted with six external experts who also completed questionnaires, 17 care home managers and 25 care home staff responsible for DCM implementation. Data were analysed using descriptive statistics and template analysis. Results Three themes were identified: the need for expert support, practicalities of support and broader impacts of providing support. Expert support was vital for successful DCM implementation, although the five-days provided was felt to be insufficient. Some homes felt the support was inflexible and did not consider their individual needs. Practical challenges of experts being located at a geographical distance from the care homes, limited when and how support was available. Experts gained knowledge they were able to then apply in delivering DCM training. Experts were not able to accurately predict which homes would be able to implement DCM independently in future cycles. Conclusions An external expert may form a key component of successful implementation of psychosocial interventions in care home settings. Future research should explore optimal use of the expert role.